(untitled) (Bangladesh Journal of Pharmacology, 2011)
In an effort to develop potent anticonvulsant agents, we have synthesized some novel schiffs bases of 3-[2-((E)-[substituted) phenyl] methylidene amino) ethyl] amino quinoxalin-2(1H)-one and evaluated for in vivo anticonvulsant activity. All the compounds were characterized by IR, 1H NMR data. This activity was carried out on pentylenetetrazole-induced seizure model. Compounds (IIIb) and (IIIc) Showed maximum time for straub tail and clonic convulsions. That means they possess good activity compared with standard. Animals treated with compounds (IIIb) and (IIIe) were recovered from this activity.